2001
DOI: 10.21273/hortsci.36.1.120
|View full text |Cite
|
Sign up to set email alerts
|

Pollination Biology of the Muscadine Grape

Abstract: Fruit set in the muscadine grape (Vitis rotundifolia Michx.) depended on insect cross-pollination, although flowers were well adapted for selfing. Pollinizer cultivars produced about half of their optimal fruit set when selfed, but cross-pollination was needed to reach an optimal fruit set of 33.7%. Eighty-one percent of the overall fruit set in pistillate vines was attributed to insect cross-pollination; wind played only a small role. Diminished fruit set and fewer seeds per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
11
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 7 publications
1
11
0
Order By: Relevance
“…The seed number of self-pollinated 'Narince' was also relatively high in comparison with other pollination types. In studies on 18 Muscadine grapes, Sampson et al (2001) revealed that many cultivars produced fewer seeds when selfed. They further indicated that there was a profound reduction in seed set due to self-pollination in a few cultivars having pistillate flowers.…”
Section: Seed Features (Xenia)mentioning
confidence: 99%
“…The seed number of self-pollinated 'Narince' was also relatively high in comparison with other pollination types. In studies on 18 Muscadine grapes, Sampson et al (2001) revealed that many cultivars produced fewer seeds when selfed. They further indicated that there was a profound reduction in seed set due to self-pollination in a few cultivars having pistillate flowers.…”
Section: Seed Features (Xenia)mentioning
confidence: 99%
“…Only 'Carlos' in the main flowering period had a viability below 90% (Table 2). High levels of muscadine pollen viability were also found by Sampson et al (2001). However, despite the high viability, pollen grain germination was low in all cultivars, and no germination was seen in the female cultivars in either flowering period.…”
Section: Resultsmentioning
confidence: 83%
“…Pollen of female flowers has been shown to be overwhelmingly sterile in germination tests (Reimer and Detjen, 1910) and in bagging experiments in breeding work (Detjen 1917;Husmann and Dearing, 1916;Reimer and Detjen, 1910). Conversely, other pollination studies have suggested low, but significant, self-pollination can occur in female cultivars (Dearing, 1938(Dearing, , 1948Sampson et al, 2001). It has also been suggested that some female cultivars may produce small amounts of functional pollen, the evidence of which is seen by high fruit set in some female cultivars such as 'Supreme', and high fruit set in secondary flowering shoots when relatively little pollen is available from pollenizer vines.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Cultivar selection decisions require an understanding of several important factors ranging from pollination biology to end-use markets. The biology of muscadine grape pollination is of importance because currently grown cultivars are hermaphroditic, possessing perfect self-fertile flowers or they are female, possessing pistillate flowers that require pollen from a different perfect flowered cultivar for fertilization and fruit-set to occur (Goffinet et al, 2001;Sampson et al, 2001). From a marketing standpoint, cultivar selection should be based upon intended end-usages.…”
mentioning
confidence: 99%